Effects of adding nano-CeO2 powder on microstructure and hydrogen storage performances of mechanical alloyed Mg90Al10 alloy. (15th January 2019) - Li, Yaqin; Shang, Hongwei; Zhang, Yanghuan; Li, Ping; Qi, Yan; Zhao, Dongliang
Abstract: For pushing Mg-based alloys developing to the practical applications, nano-CeO2 powders were added into the mechanical alloyed (MA) Mg90 Al10 alloy. The aim of it is to improve the thermodynamics and kinetics through generating new intermetallic compound, reducing the grain size and increasing the solid solubility of Al in Mg. XRD analysis showed that adding nano-CeO2 powder causes the generation of Mg17 Al12 phase and grain refinement of the MA Mg90 Al10 + x wt% CeO2 ( x = 1, 3, 5 and 8) composites. It also increases the solid solubility of Al in Mg, while results in the reduction of Mg lattice volume. The dehydrogenation enthalpy (Δ H de ), calculated from Van't Hoff equation, is reduced from 75.43 kJ mol −1 H2 for the MA Mg90 Al10 alloy to 74.22, 72.70, 70.28 and 73.71 kJ mol −1 H2 for the MA Mg90 Al10 + x wt% CeO2 ( x = 1, 3, 5 and 8) composites, respectively. The increased grain boundaries, caused by the grain refinement and formation of the mutilphase structure, are beneficial to reduce the dehydrogenation activation energy ( E de (a)). It is obtained through Johnson-Mehl-Avrami-Kolmogorov model, which is 162.06, 121.86, 103.73, 101.83 and 109.08 kJ mol −1 H2 for the MA Mg90 Al10 + x wt% CeO2 ( x = 0, 1, 3, 5 and 8) composites, respectively. Highlights: Nano-CeO2 catalyst was added into Mg90 Al10 alloy by mechanical alloying. Adding CeO2 makes the grain refine and multiphase structure generate. Adding CeO2 causes the unit cell volume of Mg to reduce. Adding CeO2 is able to improve the activation performance. Adding CeO2 can decrease dehydrogenation enthalpy and activation energy of MgH2 .